2020
DOI: 10.18087/cardio.2020.6.n1226
|View full text |Cite
|
Sign up to set email alerts
|

Steroid pulse -therapy in patients With coronAvirus Pneumonia (COVID-19), sYstemic inFlammation And Risk of vEnous thRombosis and thromboembolism (WAYFARER Study)

Abstract: Introduction Coronavirus pneumonia not only severely affects the lung tissue but is also associated with systemic autoimmune inflammation, rapid overactivation of cytokines and chemokines known as “cytokine storm”, and a high risk of thrombosis and thromboembolism. Since there is no specific therapy for this new coronavirus infection (COVID-19), searching for an effective and safe anti-inflammatory therapy is critical.Materials and methods This study evaluated efficacy and safety of pulse therapy with high dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
0
23
1
21
Order By: Relevance
“…Разработка таких предикторов позволила бы проводить стратификацию риска, направить интервенционные исследования на пациентов с повышенным риском развития тяжёлого течения заболевания, оптимизировать распределение ограниченных человеческих и технических ресурсов в условиях продолжающейся пандемии. Более того, определение лабораторных параметров, позволяющих различать тяжелые и нетяжелые случаи, а также случаи с высоким или низким риском летального исхода, позволит значительно улучшить не только маршрутизацию пациентов, но и клинические протоколы лечения [3,4].…”
Section: Discussionunclassified
“…Разработка таких предикторов позволила бы проводить стратификацию риска, направить интервенционные исследования на пациентов с повышенным риском развития тяжёлого течения заболевания, оптимизировать распределение ограниченных человеческих и технических ресурсов в условиях продолжающейся пандемии. Более того, определение лабораторных параметров, позволяющих различать тяжелые и нетяжелые случаи, а также случаи с высоким или низким риском летального исхода, позволит значительно улучшить не только маршрутизацию пациентов, но и клинические протоколы лечения [3,4].…”
Section: Discussionunclassified
“… 64 Although high-dose glucocorticoid pulse therapy has a rapid anti-inflammatory effect, it also increases the neutrophil/lymphocyte ratio and D-dimer level, increasing the risk of thromboembolism. 65 For newly diagnosed diabetic patients, frequent use of glucocorticoids may exacerbate hyperglycemia. 66 Obata et al found that the bacterial infection rate (25%/13.1%, P = 0.041) and fungal infection rate (12.7%/0.7%, P < 0.001) during hospitalization in steroid group were significantly higher than those in non steroid treatment group.…”
Section: Oppositionmentioning
confidence: 99%
“…Состояние было расценено как прогрессирующее воспаление (развивающийся «цитокиновый шторм»), и было принято решение о проведении пульстерапии высокими дозами глюкокортикостероидов 1000 мг метилпреднизолона в течение 3 дней и затем дексаметазон 8 мг × 2 р / сут. [36]. Гидроксихлорохин отменен в связи с неэффективностью, увеличена доза спиронолактона до 50 мг / сут., добавлен бромгексин 8 мг × 4 р / сут.…”
Section: вирусемияunclassified
“…В качестве первичной конечной точки использовали динамику баллов по оригинальной шкале ШОКС-КОВИД (рис. 4) [36]. Вторичными конечными точками были:…”
Section: вирусемияunclassified
See 1 more Smart Citation